Hubungan Jenis Persalinan Terhadap Keberhasilan Inisiasi Menyusu Dini : The Relationship between the Type of Delivery and the Success of Early Breastfeeding Initiation - Widyaningsih, Ari; Khayati, Yulia Nur; Isfaizah (Universitas Ngudi waluyo, 2023)
One of the efforts to increase the success of breastfeeding is the implementation of Early Breastfeeding Initiation (IMD) by newborns to their mothers. IMD will greatly assist in the continuity of exclusive breastfeeding and duration of breastfeeding. Thus, the baby's needs will be met until the age of 2 years, and prevent children from malnutrition. The highest percentage of breastfeeding in children aged 0-23 months is 1-6 hours (35.2%). The process of starting to breastfeed in the first hour after birth / IMD is only 34.5%. IMD has increased in 2018. The proportion of IMD in children aged 0-23 months is 58.2%. Of this proportion, only 15.9% did IMD ≥ 1 hour. Childbirth is the culmination of a series of pregnancy processes. The type of delivery experienced plays an important role in supporting the successful implementation of Early Breastfeeding Initiation (IMD). Early Initiation of Breastfeeding (IMD) is an instinctive process and the right of every newborn. Early Initiation or early initiation of breastfeeding is when the baby begins to breastfeed on his own immediately after birth and is allowed skin-to-skin contact with his mother's skin for at least 1 hour. The purpose of this study was to determine the type of delivery, determine the number of babies who received IMD and determine the relationship between the type of delivery and the success of IMD. This research is a correlation analysis with a cross-sectional study approach. This research was conducted in April - May 2022. The sampling technique used total sampling. Data analysis in this study was univariate analysis and bivariate analysis using the Chi Square test with the SPSS Version 22 program (95% CI and α = 0.05). The results of bivariate analysis found that there was a significant relationship between the type of delivery and the success of IMD (p <0.001, OR 24.886, 95% CI = 6.835-90.608). Spontaneous delivery without complications increases the success of IMD by 24.88 times when compared with spontaneous delivery with complications. The birth process that the mother goes through, both normally and with complications, is not an obstacle for a baby to get his right to get breast milk at the beginning of his life. Management of the practice of Early Breastfeeding Initiation in all types of labor is no different and depends on the baby being allowed to look for the mother's nipple as early as possible. It is hoped that intervention in childbirth will be kept to a minimum so that the condition of the mother and baby becomes optimal for the success of the Early Breastfeeding Initiation (IMD) process. Abstrak Upaya untuk meningkatkan keberhasilan pemberian ASI eksklusif antara lain dengan melaksanakan Inisiasi Menyusu Dini (IMD) oleh bayi baru lahir pada ibunya. IMD akan sangat membantu dalam keberlangsungan pemberian ASI eksklusif dan lama menyusui. Dengan demikian, bayi akan terpenuhi kebutuhannya hingga usia 2 tahun, dan mencegah anak kurang gizi. Persentase tertinggi proses mulai menyusu pada anak umur 0-23 bulan adalah pada 1-6 jam (35,2%). Proses mulai menyusu pada satu jam pertama setelah lahir/IMD hanya 34,5%. IMD mengalami peningkatan pada tahun 2018. Proporsi IMD pada anak umur 0-23 bulan adalah 58,2%. Dari proporsi ini, yang melakukan IMD ≥ 1 jam hanya 15,9%. Persalinan merupakan puncak peristiwa dari serangkaian proses kehamilan. Jenis persalinan yang di alami memberikan peran penting dalam mendukung keberhasilan pelaksanaan Inisiasi Menyusu Dini (IMD). Inisiasi Menyusu Dini (IMD) merupakan proses naluriah dan hak setiap bayi baru lahir. Inisiasi Menyusu Dini (Early Initiation) atau permulaan menyusu dini adalah bayi mulai menyusu sendiri segera setelah lahir dan dibiarkan kontak kulit dengan kulit ibunya sekurangnya selama 1 jam. Tujuan dari penelitian ini adalah untuk mengetahui jenis persalinan, mengetahui jumlah bayi yang mendapat IMD dan mengetahui hubungan jenis persalinan terhadap keberhasilan IMD. Penelitian ini merupakan analitik korelasi dengan pendekatan cross-sectional study. Penelitian ini dilakukan pada bulan April - Mei 2022. Populasi pada penelitian ini adalah 91 ibu bersalin. Teknik pengambilan sampling menggunakan Total sampling. Jumlah sampel yang digunakan sebanyak 91 ibu bersalin. Analisis data dalam penelitian ini adalah analisis univariat dan analisis bivariat menggunakan uji Chi Square dengan program SPSS Versi 22 dengan ( CI 95% dan α= 0.05). Hasil analisis bivariat didapatkan ada hubungan yang signifikans antara jenis persalinan dengan keberhasilan IMD (p <0,001, OR 24,886, CI 95%= 6,835-90,608). Persalinan spontan tanpa penyulit meningkatkan keberhasilan IMD sebesar 24,88 kali jika dibandingkan dengan persalinan spontan dengan penyulit. Proses persalinan yang dilalui ibu baik secara normal maupun dengan penyulit bukan sebuah hambatan seorang bayi untuk mendapatkan haknya dalam mendapatkan ASI di awal kehidupannya. Penatalaksanaan praktek Inisiasi Menyusu Dini pada semua jenis persalinan tidak berbeda dan tergantung pada sedini mungkin bayi dibiarkan mencari putting ibu. Diharapkan intervensi dalam persalinan diupayakan seminimal mungkin sehingga kondisi ibu dan bayi menjadi optimal untuk keberhasilan proses Inisiasi Menyusu Dini (IMD).